2019
DOI: 10.1051/e3sconf/201911600020
|View full text |Cite
|
Sign up to set email alerts
|

A new funding scheme for MSW management to support WtE program

Abstract: Among many approaches to manage municipal solid waste (MSW), waste to energy (WtE) program through running a landfill gas plant is believed the best way. It deals with waste and energy problems simultaneously. However, even though it offers inevitable benefits, in Indonesia WtE program implementation is stagnant. This study proposes an alternative funding scheme to run the program, i.e. based on resident participation. The study used willingness to pay from Contingent Valuation Method to disclose the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, research in four major metropolitan cities in Ghana showed that 53.7% of households were willing to make an additional payment for improvement service [9]. In Depok, Indonesia, 86% of residents were willing to fund the waste-to-energy project, especially if they get an incentive such as an electricity bill discount [10]. The household and firms are willing to pay a premium over current tariffs for high-quality electricity service without outages in Senegal [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, research in four major metropolitan cities in Ghana showed that 53.7% of households were willing to make an additional payment for improvement service [9]. In Depok, Indonesia, 86% of residents were willing to fund the waste-to-energy project, especially if they get an incentive such as an electricity bill discount [10]. The household and firms are willing to pay a premium over current tariffs for high-quality electricity service without outages in Senegal [11].…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to reuse and recycle waste that will have an increasingly attractive economic value to strive for. The research about waste to energy (WtE), showed people wat to pay more for the solid waste management because as a return they get energy from waste [2].…”
Section: Introductionmentioning
confidence: 99%